Designed pincer ligand supported Co(ii)-based catalysts for dehydrogenative activation of alcohols: Studies on N-alkylation of amines, α-alkylation of ketones and synthesis of quinolines. Issue 24 (2nd June 2021) - Singh, Anshu; Maji, Ankur; Joshi, Mayank; Choudhury, Angshuman R.; Ghosh, Kaushik
Abstract : Base-metal Co-based catalysts Co1, Co2 and Co3 supported by pincer ligands were utilized for dehydrogenative activation of alcohols giving rise to N -alkylation of amines, α-alkylation of ketones and synthesis of quinolines. Abstract : Base-metal catalysts Co1, Co2 and Co3 were synthesized from designed pincer ligands L 1, L 2 and L 3 having NNN donor atoms respectively. Co1, Co2 and Co3 were characterized by IR, UV–Vis. and ESI-MS spectroscopic studies. Single crystal X-ray diffraction studies were investigated to authenticate the molecular structures of Co1 and Co3 . Catalysts Co1, Co2 and Co3 were utilized to study the dehydrogenative activation of alcohols for N -alkylation of amines, α-alkylation of ketones and synthesis of quinolines. Under optimized reaction conditions, a broad range of substrates including alcohols, anilines and ketones were exploited. A series of control experiments for N -alkylation of amines, α-alkylation of ketones and synthesis of quinolines were examined to understand the reaction pathway. ESI-MS spectral studies were investigated to characterize cobalt-alkoxide and cobalt-hydride intermediates. Reduction of styrene by evolved hydrogen gas during the reaction was investigated to authenticate the dehydrogenative nature of the catalysts. Probable reaction pathways were proposed for N -alkylation of amines, α-alkylation of ketones and synthesis of quinolines on the basis of control experiments and detection of reaction intermediates.